2022
DOI: 10.4103/npmj.npmj_141_22
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Implantations in Jordan

Abstract: Aims: This study aims to carry out a retrospective analysis of demographic information and post-operative complications with special emphasis on complications related to the soft tissue over the implanted device in patients who underwent cochlear implantation. Settings and Design: Retrospective study. Patients and Methods: We conducted a retrospective review of 840 patients who had cochlear implants at our c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…This has been linked to various factors, including a lack of awareness, access to educational resources, social support, and the ability to attend appointments [ 20 ]. Regarding hearing impairment, parental education and income levels are critical factors for early intervention [ 21 ]. In our study, we found that most of the patients were aged 1 to 10 years, indicating that they received CI at a young age despite coming from rural areas (83.56 %) with lower socio-economic levels (97.26 %).…”
Section: Discussionmentioning
confidence: 99%
“…This has been linked to various factors, including a lack of awareness, access to educational resources, social support, and the ability to attend appointments [ 20 ]. Regarding hearing impairment, parental education and income levels are critical factors for early intervention [ 21 ]. In our study, we found that most of the patients were aged 1 to 10 years, indicating that they received CI at a young age despite coming from rural areas (83.56 %) with lower socio-economic levels (97.26 %).…”
Section: Discussionmentioning
confidence: 99%